Theoretical considerations on germline mosaicism in Duchenne muscular dystrophy. - Grimm, T (1990)
A newly formulated mutation selection equilibrium for lethal X linked recessive traits such as Duchenne muscular dystrophy is presented, which allows for both male and female germline mosaicism. Estimates of the additional parameters used are given, thus allowing the incorporation of germline mosaicism into the calculation of genetic risks.